Increasing the discrimination power of a mitochondrial DNA control region by using hypervariable region 2 polymorphisms, as illustrated in Tai populations of Northern Thailand - Chaiwat Kriengchutima (2018)
Copyright © 2015. ScienceAsia. Nucleotide sequences of the mitochondrial DNA hypervariable region 2 (HVR2) of five Tai speaking populations, Khuen, Lue, Tai Yai, Yong, and Yuan, living in the upper northern part of Thailand were analysed. Based on a comparison of 268-bp sequences in 124 people, 32 polymorphic sites, and 52 different sequence types were observed. The HVR2 possessed lower polymorphism than HVR1 of the same populations. However, when the two regions were combined, the discrimination power increased and could distinguish most of the Tai populations as well as separate the Tai from the neighbouring Mon-Khmer speaking populations. The Tai showed fewer genetic differences than those of the Mon-Khmer. This might have been a result of the admixture process across the Tai ethnic groups. The increasing of genetic polymorphism and discrimination power of the combined HVR1 and 2 data would enhance the accuracy and efficiency of personal and ethnicity identifications.